ASSESSING THE EFFECTIVENESS OF CSR PRACTICES: A STUDY ON SOUTH EASTERN COALFIELDS LIMITED, BILASPUR - Tiwari, Shruti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An industry heavyweight, South Eastern Coalfields Limited (SECL) in Bilaspur is the subject of this research study that evaluates the efficacy of its CSR initiatives. The study's overarching goals are to ascertain whether or not SECL's CSR practices are in line with larger CSR concepts and objectives and assess the ways in which these activities have affected local people and the environment.This research makes use of a mixed-methods strategy, integrating quantitative results from surveys of local stakeholders (such as workers, residents, and government officials) with qualitative information gleaned via in-depth interviews and document review. Important parts of SECL's CSR initiatives, including health and education programs, community development, environmental management, and economic benefits, are the subject of the study.Improvements to community infrastructure, educational opportunities, and healthcare services have been directly attributed to SECL's CSR programs, according to the findings. Still, questions about stakeholder involvement and the projects' long-term viability persist. While SECL's CSR procedures are in line with industry norms and have a beneficial influence on local development, the analysis also shows that there is room for improvement in terms of transparency and targeting.At the conclusion of the article, we suggest several ways that SECL might improve its CSR practices. These include making sure that programs are sustainable, communicating with stakeholders better, and measuring and reporting CSR achievements better. This research offers valuable information for corporate social responsibility practitioners and policymakers, while also adding to our knowledge of how successful CSR is in the mining industry.